Força dos Músculos Rotadores do Ombro em Indivíduos Saudáveis/ Rotator Cuff Muscle Strength in Healthy Individuals - Paulo José Oliveira Cortez; José Elias Tomazini; Mauro Gonçalves (Hospital de Clínicas de Itajubá, 2011)
Introdução: A diminuição da capacidade de exercer esforços por parte dos músculos rotadores pode criar uma variedade de problemas. O conhecimento preciso do nível de força muscular de um indivíduo é importante, tanto para a avaliação da capacidade funcional ocupacional, como para uma apropriada prescrição de exercícios atléticos e de reabilitação. Percebe-se escassez de informação sobre as articulações do ombro, bem como os fatores envolvidos na força muscular dessa região. O objetivo deste estudo foi comparar a força gerada pelos músculos do manguito rotador entre o membro superior direito e o membro superior esquerdo em indivíduos saudáveis. Métodos: Participaram do estudo 22 sujeitos do sexo masculino, com idade de 18 e 19 anos, militares, saudáveis e sem história clínica de patologia ortopédica ou qualquer tipo de lesão no sistema musculoesquelético. Foram aplicados dois testes de força: Rotação Interna e Rotação Externa. Resultado : A força média de rotação interna no membro superior direito (MSD) foi maior que a força média de rotação interna no membro superior esquerdo (MSE) (p=0,723) e a força de rotação externa no MSD foi menor que a força média de rotação externa no MSE (p=0,788). Não houve diferença estatística na comparação dos valores de força de todos os testes de força isométrica. Conclusão: Para amostra estudada e metodologia utilizada na avaliação da força muscular, não houve diferença estatística na comparação da força gerada pelos músculos do manguito rotador do membro superior direito e do membro superior esquerdo. Rotator Cuff Muscle Strength in Healthy Individuals  Introduction: Decreased ability to exert efforts by the rotator muscles can create a variety of problems. The precise knowledge of the level of muscular strength of an individual is important for both the functional capacity evaluation for occupational as an appropriate exercise prescription and rehabilitation of athletic. It is perceived scarcity of information on the shoulder joints as well as factors involved in muscle strength in this region. Objective: Develop a device for measuring the strength generated by the muscles of the upper limbs and the verification of efficiency and adaptability of this device through a comparative study of muscle strength in healthy subjects. Methods: The study included 22 male subjects, aged 18 and 19 years, military personnel, body mass between 57.7 and 93 kg (71.8 ± 9.45 kg) and height between 1.67 and 1.90 m (1.75 ± 0.06 m), healthy and without a history of orthopaedic disease or any kind of damage to the musculoskeletal system. Three strength tests were applied: Internal Rotation and External Rotation. For each type of effort three maximum voluntary contractions were required for 10 seconds, with an interval of 30 seconds between each contraction.  Results: Internal rotation in the right upper limb (RUL) was higher than the average strength of internal rotation in the left upper limb (LUL) (p = 0, 723) and the external rotation strength in RUL was lower than the average strength of external rotation in the LUL (p=0,788).  No statistical difference in comparing the strength values of all isometric strength tests. Conclusion: For sample and methodology used to assess muscle strength, there was no statistical difference in comparing the force generated by the muscles of the rotator cuff of the right and left upper limb.